Optimalisasi Penyusunan Rencana Anggaran Biaya Pada Badan Pendidikan dan Pelatihan Kejaksaan Republik Indonesia - An Nissa Panindha; Tri Hesti Utaminingtyas; I Gusti Ketut Agung Ulupui (Jurnal Akuntansi, Perpajakan dan Auditing, 2024)
This research aims to optimize the preparation of the Cost Budget Plan (RAB), one way to achieve this by trying to operate the formula in Ms. Excel for calculating RAB in a government agency. This research method uses qualitative. The results of this research show that by using formulas in Ms. Excel can calculate RAB quickly, save time and energy and make decision making easier so it can be categorized as more effective and efficient. Based on the research purpose, in implementation to optimize the preparation of the RAB in the using formula in Ms. Excel, it is to ensure that employees have sufficient understanding of the use of formula in Ms. Excel. Suggestions from researchers require training, assistance or operators who can operate using the formula Ms. Excel, so that it can maximize the potential of this application to increase effectiveness, efficiency, accuracy and quality of agency performance